Analisis Laporan Keuangan Dalam Menilai Kesehatan Kinerja Keuangan Perusahaan Pada Pt. Bank Perkreditan Rakyat (BPR) Jateng Tahun 2013-2017 - Haninditya Nurullasari; Nanang Yusroni; Ernawati Budi Astuti (Universitas Wahid Hasyim, 2018)
Abstract This study aims to determine the level of soundness of the company's financial performance from PT. BPR in 2013-2017 using ratio analysis of capital, profitability and liquidity factors. The data analysis technique used is a quantitative descriptive analysis technique. Based on the results of data analysis and discussion shows that the financial health performance of PT. Central Java Rural Banks (BPR) in 2013-2017 viewed from the capital factor if calculated using the CAR ratio can be categorized as HEALTHY. When viewed from the profitability factor and calculated using the ROA ratio it is also categorized HEALTHY, but when seen the BOPO ratio of PT. Central Java Rural Bank in 2015-2017 is categorized as NOT HEALTHY because the resulting ratio is too high so it is inefficient. While the health level is seen from the liquidity factor of PT. Central Java Rural Bank is categorized as HEALTHY. Keywords: Soundness, Capital Adequacy Ratio (CAR), Return On Assets (ROA), Operating Expenses Against Operating Income (BOPO), Cash Ratio, Loan to Deposit Ratio (LDR) Abstrak Penelitian ini bertujuan untuk mengetahui tingkat kesehatan kinerja keuangan perusahaan dari PT. BPR Jateng Tahun 2013-2017 dengan menggunakan analisis rasio dari faktor permodalan, rentabilitas dan likuiditas. Teknik analisis data yang digunakan adalah teknik analisis deskriptif kuantitatif. Berdasarkan hasil analisis data dan pembahasan menunjukkan bahwa kesehatan kinerja keuangan PT. Bank Perkreditan Rakyat (BPR) Jateng pada tahun 2013-2017 dilihat dari faktor permodalan apabila dihitung dengan menggunakan rasio CAR dapat dikategorikan SEHAT. Jika dilihat dari faktor rentabilitas dan dihitung dengan menggunakan rasio ROA juga dikategorikan SEHAT, namun apabila dilihat rasio BOPO PT. Bank Perkreditan Rakyat Jateng tahun 2015-2017 dikategorikan TIDAK SEHAT karena rasio yang dihasilkan terlalu tinggi sehingga tidak efisien. Sedangkan tingkat kesehatan dilihat dari faktor likuiditas PT. Bank Perkreditan Rakyat Jateng dikategorikan SEHAT. Kata Kunci : Tingkat Kesehatan, Capital Adequacy Ratio (CAR), Return On Assets (ROA), Beban Operasional Terhadap Pendapatan Operasional (BOPO), Cash Ratio, Loan to Deposit Ratio (LDR)